M2 muscarinic receptor activation inhibits cell proliferation and migration of rat adipose‐mesenchymal stem cells. Issue 7 (23rd January 2018) - Piovesana, Roberta; Melfi, Simona; Fiore, Mario; Magnaghi, Valerio; Tata, Ada Maria
Abstract : Mesenchymal stem cells (MSCs), also known as stromal mesenchymal stem cells, are multipotent cells, which can be found in many tissues and organs as bone marrow, adipose tissue and other tissues. In particular MSCs derived from Adipose tissue (ADSCs) are the most frequently used in regenerative medicine because they are easy to source, rapidly expandable in culture and excellent differentiation potential into adipocytes, chondrocytes, and other cell types. Acetylcholine (ACh), the most important neurotransmitter in Central nervous system (CNS) and peripheral nervous system (PNS), plays important roles also in non‐neural tissue, but its functions in MSCs are still not investigated. Although MSCs express muscarinic receptor subtypes, their role is completely unknown. In the present work muscarinic cholinergic effects were characterized in rat ADSCs. Analysis by RT‐PCR demonstrates that ADSCs express M1‐M4 muscarinic receptor subtypes, whereas M2 is one of the most expressed subtype. For this reason, our attention was focused on M2 subtype. By using the selective M2 against Arecaidine Propargyl Ester (APE) we performed cell proliferation and migration assays demonstrating that APE causes cell growth and migration inhibition without affecting cell survival. Our results indicate that ACh via M2 receptors, may contribute to the maintaining of the ADSCs quiescent status. These data are the first evidence that ACh, via muscarinic receptors, might contribute to control ADSCs physiology. Abstract : Autocrine or paracrine release of ACh in the stem niche, negatively modulates cell proliferation, and migration of adipose mesenchimal stem cells (ADSCs) via activation of M2 acetylcholine muscarinic receptors. The modulated activity of these receptors may impair in the ADSCs action of growth factors, contributing to the balance between the quiescent phase and the proliferative, migratory, and differentiating phases.